Bromélia: bancada multifuncional para laboratórios de Astronomia - Pereira, Paquisa Melo de Oliveira (2016)
This project aims at the development of educational kits for science laboratories, with a focus on astronomy as a complementary tool of the lectures of Science. In the educational field, the changes that have been derived from the incorporation of experimental classes have provided an opportunity for rethinking of the relationship between teaching and learning. In the area of science, this can offer a great contribution in teaching practices. For this reason, its use can not be done at random and disconnected from an educational design. The challenge is to produce knowledge related to the theory and practice within the school context and day-to-day lives of students. We intend to follow this approach with Astronomy and provide critical experiential opportunities that will facilitate learning. This will clarify concepts sometimes misunderstood solely by lecture and make connections between diverse disciplines, such as Geography, Physics, Mathematics, Biology and Chemistry. Ultimately, It's expected that the teaching of science through experiments using astronomy as a pillar will be of great benefit. It is well known that this area of science arouses much curiosity in children of all ages. It is expected that the presentation of scientific concepts using experiments, with interconnections with Astronomy, will increase the comprehension of the students. To achieve this, the developed of new educational kits, which are able to connect the student with everyday concepts of astronomy, should motivate the student about learning more about the scientific disciplines and help the students by stimulating their creativity and expand their critical reasoning. In specific, the proposed kits to the areas cited are: Electrotechnology, Seasons and Pasnpermia. We will emphasize the Chemistry - Panspermia and Geography - Seasons kit, as well as display the details of a kit to assemble electrotechnology to evaluate the proposed methodology.